Kajian Yuridis Sosiologis Terhadap Penegakan Hukum Lingkungan Akibat Pencemaran Air : Sociological Legal Study of Environmental Law Enforcement Due to Water Pollution - Istiana; Dominikus Rato (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Nowadays, environmental problems due to water pollution have become a burden in themselves, where law enforcement and community participation are of course important in environmental safety and sustainability. Law as a pioneer of change in social groups aims to realize a sense of justice. So, to produce a sense of justice, of course the roles of both law enforcers and the community must be in harmony to make this happen. So the theory of justice needs to be applied in environmental law enforcement mechanisms. Permasalahan lingkungan akibat pencemaran air menjadi beban tersendiri dalam dimanaka penegakan hukum, peran serta masyarakat tentunya menjadi hal penting dalam keselamatan dan kelestarian lingkungan. Hukum sebagaipelopor perubahan dalam kelompok masyarakat yang tak lain bertujuan untuk mewujudkan rasa keadilan. Sehingga untuk menghasilkan rasa keadilan tentunya peran kedua antaran penegak hukum dan masyarakat harus selaras untuk mewujudkan. Sehingga teori keadilan perlu diterapkan dalam mekanisme penegakan hukum lingkungan